SLOPE RECOVERY: STABILIZATION AND EROSION CONTROL STRATEGIES ON HIGHWAY MT-358 (REMUNOM, 2025)
Slopes are fundamental structures in highways, responsible for providing stability to the pavement soil and preventing issues such as erosion and landslides. This study aims to examine the recovery of a slope located in the MT 358 highway, near the municipality of Tangará da Serra/MT, which experienced a mass movement caused by intense rainfall. The recovery process included regrading the area, adjusting the slope inclination for greater stability, reconstructing the drainage system, and applying grass mats for erosion control. The results demonstrated that the interventions were effective, ensuring the stability of the slope and the safety of the highway up to the conclusion of the study.